(3TLhf GdMOjK aj CNHGQ GdMTjTI GdbOje hGdMOjKs
(3ChdgG (B:s
(3Ef TLQI GdMTjTI GdedYhfg bO cGf dgG ONd cHjQ ai MjGI HYV GdCbhGe GdfGFjI s
(3BNQgG (B:s
(3fbOJ ai jejfi Ci de jbY Ydjg WdGb hZQVg Gfg GSJab CMO GdabgGA ajeG Yedg aGaJGg HGf dGMfK ai Gdjejf dGNJdGa eMd GdGSJYeGd s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI aDGO GdChd (B(5965) s
Keywords: (3GdSjGSI hGdGLJeGYs